W18O49 nanowires-graphene nanocomposite for asymmetric supercapacitors employing AlCl3 aqueous electrolyte - Thalji, Mohammad R.; Ali, Gomaa A. M.; Liu, Porun; Zhong, Yu Lin; K. F., Chong (Elsevier, 2021)
W18O49 nanowires (NWs)-reduced graphene oxide (rGO) nanocomposite is examined as a new active material for supercapacitors electrode, which reveals its high specific capacitance and excellent rate performance in AlCl3 aqueous electrolyte. Electrochemical studies show that the presence of rGO enhances Al3+ ions diffusion in the nanocomposite, thus provides more ions for intercalation pseudocapacitance. The fabrication of asymmetric supercapacitor W18O49 NWs-rGO//rGO demonstrates high specific capacitance of 365.5 F g−1 at 1 A g−1 and excellent cycling stability with 96.7% capacitance retention at 12,000 cycles. Interestingly, it delivers high energy density of 28.5 Wh kg−1 and power density of 751 W kg−1, which is the highest energy density value for all reported W18O49-based supercapacitor device. The work explores W18O49 NWs-rGO nanocomposite as a new electrode material for supercapacitors application with superior electrochemical performance, which may open up a new direction for high-performance energy storage in Al3+ electrolyte.